The Impact of Training and Development on the performance of employees: The case of Bureau of public service and human resource development in Sidama National Regional State, South Ethiopia - Bagajjo, Wosenyeleh Semeon (Technium Social Sciences Journal, 2022)
The study was focusing on the impact of training and development on employees’ performance at the Bureau of Public Service and Human Resource Development. The overall objective of the study was to determine the effect of training and development on employees’ performance. The study used mixed approach and applied both primary and secondary data sources. The primary data collected from BOPSHRD through self-administered questionnaire for 156 selected experts and middle level managers through simple random sampling technique and semi- structured interview question exploited for human resource process owner and training coordinator through interview. The collected data were analyzed using statistical tools (SPSS-Version 23). Both descriptive and inferential statistics were used for the data analysis. The findings showed that training and development were positively correlated and claimed statistically significant relationship with employees’ performance. The study concluded that training and development have positive effect on employees’ performance. The findings of the study also indicated that there was no sounding and effective training and development practices in the area of the study, consequently the result disclosed the given training and development processes have been unsystematic. Therefore, the researcher recommended that the top Management and other training coordinators should apply systematic and authentic training and development practices. All in all, the study recommended that training and development have to be strategic and systematic in order to achieve bureau’s desires and objectives.